Mindfulness and its relationship to academic achievement among university students - Alomari, Hassan (Frontiers in Education, 2023)
The primary objective of this study was to assess the degree of mindfulness among university students based on their gender and academic achievement level. To accomplish this, the Five Facet Mindfulness Questionnaire (FFMQ) was employed, consisting of 39 items categorized into five factors: observation, description, acting with awareness, nonjudging, and nonreactivity. The questionnaire was initially translated into Arabic and applied to a pilot sample of 60 male and female students to assess item characteristics and verify the validity and reliability of the scale. Following the finalization of the questionnaire, it was administered to a cluster sample of 489 male and female students from public universities. The results indicated a moderate level of mindfulness across all five domains, with no significant gender differences. Furthermore, the study revealed that students with higher academic achievement displayed greater mindfulness. However, the relationship between mindfulness and academic achievement was weak, explaining less than 1% of the variance in academic performance